2011
DOI: 10.1097/iop.0b013e31820d1f7b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Canalicular Entrance Into the Lacrimal Sac: An Anatomical Study

Abstract: This study provides direct anatomical evidence that the prevalence of separate canalicular orifices in the lacrimal sac is lower than previously reported (<1%). Additionally, the presence of a valve-like structure at the canalicular/lacrimal sac junction is common. These observations can potentially play a role in evaluating and treating lacrimal system pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
1
24
2
Order By: Relevance
“…Therefore, based on the anatomical study by Orhan et al, the present study used the diameter at 3 mm from the dome of the lacrimal sac to determine the area of the upper portion of the lacrimal sac and the diameter at 7 mm from the dome to determine the area of the lower portion of the lacrimal sac. Many researchers have reported [18][19][20] that mucosal folds exist at the canalicular entrance of the lacrimal sac and that these mucosal folds can open and close when the eyelid opens or closes. Using a high-definition video camera, Kakizaki et al [21] observed the changes in the internal canalicular orifice along with opening and closure of the eyelid after dacryocystorhinostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the anatomical study by Orhan et al, the present study used the diameter at 3 mm from the dome of the lacrimal sac to determine the area of the upper portion of the lacrimal sac and the diameter at 7 mm from the dome to determine the area of the lower portion of the lacrimal sac. Many researchers have reported [18][19][20] that mucosal folds exist at the canalicular entrance of the lacrimal sac and that these mucosal folds can open and close when the eyelid opens or closes. Using a high-definition video camera, Kakizaki et al [21] observed the changes in the internal canalicular orifice along with opening and closure of the eyelid after dacryocystorhinostomy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Management of common canalicular obstruction poses unusual problems and has largely been unsatisfactory. 4,11 The conjunctivo-DCR, consisting of Jones tube placement, 5 is a bypass surgery that is standard for irreparable proximal lacrimal obstruction. 10 The success rate of this procedure varies from 75% to 80%, and results may not be universal.…”
Section: Discussionmentioning
confidence: 99%
“…In our case series, such an obstruction was diagnosed preoperatively in all cases, and therefore, we anticipated the presence of thick membranous obstruction. 11 Chronic inflammation can result in fibrosis and adherence of this valve to the mucosa resulting in obstruction at distal common canaliculus. 11 Chronic inflammation can result in fibrosis and adherence of this valve to the mucosa resulting in obstruction at distal common canaliculus.…”
Section: Discussionmentioning
confidence: 99%
“…The tip of the probe may get caught within the mucosal folds of the CIO or lacrimal sac mucosa, falsely suggesting an obstruction, an issue noted by others. 23,24 However, gentle redirection of the probe under direct visualization of the CIO and adequate lateral traction of the eyelid will generally obviate this problem. Although DCG and DSG are not routinely used in the setting of CCO, we employed these tests in addition to clinical diagnostic techniques to ensure the inclusion of only true CCO in this prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Transcanalicular techniques to address CCO have a low morbidity and limited invasiveness, therefore the need for a DCR may be questioned when the pathology is proximal to the lacrimal sac. However, direct visualization of the CIO allows one to distinguish mucosal folds more reliably from true membranes, 23 and helps to avoid misdirection of the lacrimal probe or engagement of common canalicular or distal canalicular walls. Open lacrimal techniques allow more precise guidance of the trephine or lacrimal probe to emerge at the CIO, reducing the risk of creating a false passage.…”
Section: Discussionmentioning
confidence: 99%